2019
DOI: 10.1371/journal.pone.0227133
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of tissue and serum parameters of bone metabolism in a series of orthopaedic patients

Abstract: Bone diseases represent an increasing health burden worldwide, and basic research remains necessary to better understand the complexity of these pathologies and to improve and expand existing prevention and treatment approaches. In the present study, 216 bone samples from the caput femoris and collum femoris of 108 patients with degenerative or dysplastic coxarthrosis, hip fracture, or osteonecrosis were evaluated for the proportion of trabecular bone (TB) and expression of parathyroid hormone (PTH) type 1 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…The age-associated increase of serum levels of bioactive sclerostin detected in this study is in line with most previous investigations, all of them using one of the former sclerostin ELISA assays. Except for an in vitro study which could not find age-related changes in sclerostin expression [20], most clinical studies detected an age-associated increase of serum levels of sclerostin [6,[11][12][13][14]; however, Dovjak et al [7] and Moriwaki et al [9] found an age-associated increase of serum sclerostin in men only. Study groups [10,21,22] that investigated solely postmenopausal women could not detect an association between serum sclerostin and age; however, this study revealed a positive association of bioactive sclerostin with age in men and women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The age-associated increase of serum levels of bioactive sclerostin detected in this study is in line with most previous investigations, all of them using one of the former sclerostin ELISA assays. Except for an in vitro study which could not find age-related changes in sclerostin expression [20], most clinical studies detected an age-associated increase of serum levels of sclerostin [6,[11][12][13][14]; however, Dovjak et al [7] and Moriwaki et al [9] found an age-associated increase of serum sclerostin in men only. Study groups [10,21,22] that investigated solely postmenopausal women could not detect an association between serum sclerostin and age; however, this study revealed a positive association of bioactive sclerostin with age in men and women.…”
Section: Discussionmentioning
confidence: 97%
“…Almost all investigations found higher sclerostin levels in males than in females [6][7][8][9]. Despite a few contradicting data [9,10], most clinical studies detected an age-associated increase of serum levels of sclerostin [6,[11][12][13][14]. Although other companies also developed an assay, the majority of these studies used the quantitative sandwich enzyme-linked immunosorbent assay (ELISA) by Biomedica; however, by now the company has developed a new, a bioactive sclerostin ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Increased PTH1R expression promote the bone resorption rate via activation of osteoclasts, whereas OPG protects the bone from resorption by binding to RANKL and TRAIL, thus inhibiting osteoclastogenesis. (30) The low levels of PTH1R and OPG observed in our study re ect a dramatic diminished but still present bone metabolism, as a consequence of the cell freezing. In accordance with the notion, that ABF cells stored at -80° C demonstrate decreased metabolism, they also express lower OPG levels.…”
Section: Resultsmentioning
confidence: 49%
“…As reviewed by Vogel et al (22) 60% of the variation in protein concentration that cannot be explained by measuring mRNAs alone is at least partially due to translation and protein degradation. Other works have also observed the lack of association between OPG, PTH, and RANKL gene expression in bone and serum levels (23,24).…”
Section: Discussionmentioning
confidence: 97%